Transformasi Diplomasi Kesehatan: Studi Kasus Indonesia Philippines Business Health Forum (IPBHF) 2025 dalam Perluasan Kerja Sama Kedua Negara - Shevanya Aprilia Tesalonika Chajatun; Tunjung Wijanarka; Triesanto Romulo Simanjuntak (Jurnal Kajian dan Penelitian Umum, 2026)
This study examines how Indonesia’s health diplomacy has transformed into economic diplomacy through the Indonesia-Philippines Business Health Forum (IPBHF) 2025. The research employs a descriptive qualitative approach using a document-based case study method. Primary data were obtained through interviews, while secondary data were collected from news articles, online sources, journals, books, and other relevant literature. The analysis is conducted using the theories of Liberalism, Health Diplomacy, Hybrid Diplomacy, and the concept of International Cooperation. The findings indicate that IPBHF 2025 represents a concrete manifestation of Indonesia’s hybrid diplomacy by integrating health and economic sectors, as reflected in the signing of the HIPELKI-Instatech Memorandum of Understanding (MoU), business matching activities, and the promotion of Indonesian medical devices in the Philippine market. This transformation demonstrates that Indonesia’s health diplomacy has evolved into an instrument of economic diplomacy that strengthens the competitiveness of the national medical device industry while enhancing Indonesia’s positive image within ASEAN. Therefore, IPBHF 2025 illustrates that the involvement of both state and non-state actors in health diplomacy can expand bilateral cooperation and support the achievement of Indonesia’s national economic interests through the health sector.